Increased alpha-fetoprotein concentration in association with ileal adenocarcinoma complicating Crohn's disease. Issue 3 (March 1984) - Leader, M; Jass, J R
Abstract : A considerably raised serum alpha-fetoprotein concentration was found in a patient with an ileal adenocarcinoma. alpha-fetoprotein was shown in both the primary tumour and the hepatic metastases by an immunoperoxidase technique. A raised alpha-fetoprotein concentration in association with ileal adenocarcinoma has not been described previously, and it is notable that the first such case should occur as a complication of longstanding Crohn's disease.